ADVANCED STAGE OF ENDOMETRIOSIS AND ITS TRANSITION TO MALIGNANCY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the advanced stage of endometriosis and its potential transformation into a malignant tumor. The discussion focuses on risk factors, pathogenesis, modern diagnostic methods, and treatment strategies. Special attention is given to the role of chronic inflammation, hormonal changes, and genetic mutations in malignancy processes. New approaches to the early detection of oncogenic transformations of endometriotic foci using molecular and immunohistochemical methods are reviewed. Prospective treatment methods, including targeted and immunotherapy, aimed at reducing the risk of malignant tumor development in endometriosis, are analyzed.